Communication strategies in cosmetic surgery websites: an application of Taylor's six-segment message strategy wheel. - Ahn, Ho-Young Anthony; Wu, Lei; Taylor, Ronald E (Health marketing quarterly, 2013)
Using Taylor's six-segment message strategy wheel as a theoretical framework, this study examines the communication approach (transmission or ritual) and message strategy (ego, social, sensory, routine, acute need, or ration) of cosmetic surgery websites. A content analysis revealed a fairly even division between transmission and ritual approaches. Ration strategy was the exclusive strategy in the websites adopting a transmission approach. No routine or acute need strategies were observed. Websites incorporating the ritual approach used ego, social, and sensory strategies. Human female models and natural objects were incorporated to deliver emotional persuasion. Implications for cosmetic surgery web marketers are discussed.
Keywords: *Communication; *Marketing of Health Services/mt [Methods]; *Surgery, Plastic; Communication; Emotions; Female; Humans; Internet; Marketing of Health Services; Models, Theoretical; Motivation; Surgery, Plastic; Surgery, Plastic/px [Psychology]; Taylor's six-segment message strategy wheel; United States; article; content analysis; cosmetic surgery; dept.com; emotion; female; financial management; human; interpersonal communication; methodology; motivation; physician advertising; plastic surgery; psychological aspect; theoretical model